Studies on diode-pumped solid-state vanadate lasers - Peng, Xiaoyuan. (2008)
The objective of this project is to design, analyze, optimize and develop a diode-end-pumped solid-stayr laser with good beam quality, high efficiency, high stability, high reliability at high repetition rate output power of the DPSS laser in TEM00 mode is in the range of 10W for IR and green wavelength.